Anatomy Laboratory Postdoctoral Training during COVID-19 Pandemic in Europe: Challenges and Solutions - Aspalilah Alias; Razif Abas (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2024)
Indexed by Scopus/MyCite